Sanctions against Russian gas would not endanger EU or German gas supply - Franziska Holz; Lukas Barner; Claudia Kemfert; Christian R. von Hirschhausen (DIW Weekly Report, 2024)
As a result of the Russian attack on Ukraine, natural gas prices skyrocketed in 2022 and Germany in particular felt the impact of its strong dependency on Russia. Prices have since relaxed, the European natural gas industry has overcome the uncertainty due to the energy crisis in 2022, and the industry also survived the slump in Russian natural gas imports without supply interruptions. However, Russia continues to export liquefied natural gas (LNG) to Europe and still has some countries in Central and Eastern Europe under control in terms of energy policy, which has so far prevented EU sanctions on Russian natural gas exports. Both the German and European natural gas supplies would be secure in the long term without Russian imports, as shown by model calculations using the Global Gas Model which depicts the global natural gas industry in great detail. Security of supply is, thus, not standing in the way of further EU sanctions against Russia. Increased efforts to save energy and a timely natural gas phase-out would reduce dependency on gas imports, which will also contribute to climate change mitigation.
Keywords: C61; L71; L95; Q34; 330; global gas markets; Europe; Russia; energy security